Defining the predator landscape of northeastern British Columbia. - Milakovic, Brian (Author); Parker, Katherine (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2008)
My research represents the predator (wolves, Canis lupus, and grizzly bears, Ursus arctos) component of a collaborative endeavor to examine processes that structure the multi-predator multi-prey system of the undisturbed Besa-Prophet watershed in the northern Rocky Mountains, northeastern British Columbia, Canada. It incorporated seasonal movements and range use, resource selection models, and isotopic assessments of prey selection to better understand predator use of the landscape. Mean annual range sizes of five wolf packs and 13 female grizzly bears were 801[plus or minus]118 km² and 334[plus or minus]33 km², respectively. Sizes of annual, denning and late-summer ranges of wolves were proportional to the extent of conifer habitat and related to pack size, whereas winter and late-winter ranges appeared to be a function of movement rates. Most wolf packs used lower elevations during the winter and late-winter seasons and higher elevations during denning, late summers, and fall. Wolves showed highest selection for areas of high habitat diversity. They tended to select shrub habitats year-round and burned habitat classes seasonally, and avoided confer classes. For grizzly bears, sizes of annual home ranges were inversely related to the extent of available Elymus-dominated burns; and seasonal ranges and movement rates were a function of family status. Grizzly bears generally were found at higher elevations during spring, lower elevations during fall, and across elevational gradients during summer. Shrub and burned habitat classes were important to grizzly bears year-round, and conifer classes were consistently avoided. Habitat selection by grizzly bears was best predicted from habitat class, elevation, aspect, and vegetation diversity. Moose (Alces alces) and elk (Cervus elaphus) dominated the diets of wolves. Both male and female grizzly bears increased meat intake (primarily elk) in the fall and males consumed more meat that females throughout the year. Estimates of prey proportions in the diets of wolves and ...